Maternal dietary carotenoids mitigate detrimental effects of maternal GnRH on offspring immune function in Japanese quail (Coturnix japonica) - Peluc, Susana Ines (2013)
Maternal resources deposited in eggs can affect the development of several offspring phenotypic traits and result in trade-offs among them. For example, maternal androgens in eggs may be beneficial to offspring growth and competitive ability, but detrimental to immunocompetence and oxidative stress. In contrast, maternal antioxidants in eggs may be beneficial if they mitigate oxidative stress and immunosuppressive effects of androgens. We investigated possible interactive effects of maternal steroids and carotenoids on aspects of offspring physiology and phenotype, by simultaneously manipulating levels of androgens (via gonadotropin-releasing hormone, GnRH-challenges) and carotenoids (via diet supplementation) in captive female Japanese quail Coturnix japonica during egg laying. Carotenoid supplementation of hens, which elevates yolk concentrations of carotenoid and vitamins A and E, enhanced egg hatching success, offspring survival to age 15 d, and size of the bursa of Fabricius in offspring. In contrast, repeated maternal GnRH challenges, which elevated yolk testosterone concentrations, enhanced offspring neonatal size, but negatively affected bursa size. However, interaction among the treatments suggests that the positive effect of maternal carotenoid supplementation on plasma bactericidal capacity was mediated by maternal GnRH challenges. Chicks originating from carotenoid-supplemented hens were less immunosuppressed than those originating from carotenoid-supplemented + GnRH-challenged hens, which were less immunosuppressed than chicks from GnRH-challenged females not supplemented with carotenoids. Females availability of carotenoid enriched diets allows them to enhance the development of offspring immune system via carotenoids and vitamins deposited in egg yolks and offset detrimental effects of androgens deposited by GnRH-challenged females.